LEGAL RESPONSIBILITY PRESCRIBING OFF-LABEL DRUGS: IS SPAIN DIFFERENT?. Issue 1 (14th December 2015) - Peire, Maria A.
Abstract : – In Spain the compassionate use and off-label prescription, are both regulated in the same law: the Royal Decree 1015/2009. This norm facilitates the access to drugs in specific clinical situations, similar to US regulation and in a different way to the UE regulation. – It is a legal practice to prescribe in an off-label manner if the following requirements are followed: there are no authorized therapeutic alternatives, prescribed in health centers, when access to these drugs is provided through a protocol of use after justifying (written) and properly informing (verbal) and obtaining the patient's consent. – When prescribing off-label the doctor's decision is based on contrasted scientific evidence (not merely on personal intuition nor personal experience). In fact, this anticipates an eventual update of the data sheet for new indications or populations, unlike the French situation where they have the ATU (Temporary Utilization Authorization). – In Spain the holder of the Marketing Authorization is obliged not to promote or advertise the use of the drug in different conditions to those approved (unlike the USA regulation). – The jurisprudential analysis from the Spanish Courts states that the doctor's responsibility is equal than that concerning on-label prescription, that is, only in the case of bad medical praxis (as in the USA). The most important cause of sentencing were: the lack of informed consent, lack of control of the medication and lack of correct follow-up of the illness, whereas this does not include the drug, dose, duration or even the patient's age. – In European Union the general rule dictated by the Courts is to permit off-label use if this is according to the best medical practice (lex artis ad hoc). Even more, there are some specific cases (in Germany, like in the USA) where it is possible to generate doctor's responsibility for no prescribing in a off-label manner.